Analisis Keuntungan Proyek Menggunakan Metode Roi Pada Proyek Pembangunan Perumahan Subsidi Permata Alam Kecamatan Diwek Kabupaten Jombang - Ahmad Dhiyaur Rahman; Totok Yulianto; Titin Sundari; Meriana Wahyu Nugroho (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Infrastructure development in Jombang Regency has increased, after the city returned to normal from the Covid outbreak over time. The natural gem subsidized housing project was built on an area of ​​7,410 m2. This landed house was built with Type 30/60 with a total of 71 housing units. This project was built by PT SAMI KARYA. In this research, data collection was obtained from developers such as weekly reports, daily reports, work schedules, RAB, and actual costs. In 2023, demand for houses in Jombang Regency will increase drastically because there are still many people who need a place to live. The methods used are Return of investment, Internal rate of return and Benefit cost ratio. The ROI calculation method is concluded to be still in profitable status as a long-term investment and can be used to invest in subsidized housing development projects with an ROI value above 16.19% as a return on investment parameter, but after carrying out a trial calculation, a profit value of 389 is obtained. % and of course achieve, even exceed the target.